(untitled) (E Conference Zone, 2022)
The article is dedicated to associating with the pedagogical basis of teaching methods in philological education of the higher education system, the current state of use of educational tasks, in particular, practical lessons in linguistics, didactic tasks in lessons on the theory and practice of methodological approaches in linguistics. teaching methods for improvement were analyzed